CaCO3-Reformulated Interlocking Bricks: Physical Characterization and Their Antibacterial and Anti-Inflammatory Potential for Healthy Housing - Djati, Muhammad Sasmito; Rachmawati, Turniningtyas Ayu; Anggraini, Retno; Zacoeb, Achfas; Rifa`i, Muhaimin; Minang, Bony Zulkarnaen; Kusuma, Kavana Hafil; Prima, Alex; Christina, Yuyun Ika (Biotropika: Journal of Tropical Biology, 2025)
Calcium carbonate (CaCO3) has many benefits for medicine, manufacturing, and nanotechnology due to its antibacterial and anti-inflammatory properties. Interlocking bricks (i-bricks) are widely used in sustainable housing for efficient air circulation and reducing humidity inside the house. If CaCO3 is mixed with interlocking brick, it can inhibit bacterial growth, leading to a healthier indoor environment. Therefore, this study aimed to investigate the physical characterization and antibacterial activity of CaCO3-reformulated i-brick, and its anti-inflammatory potential in mice infected with Salmonella typhimurium. The physical characterization of CaCO3-reformulated i-brick (F1-F10 formulas), including its density, compression, and absorption, was analyzed. The inhibitory activity of CaCO3-reformulated i-brick on S. typhimurium growth was determined using a linear regression equation between culture age and cell density values. BALB/c male mice were randomly divided into four groups (n=4): healthy mice (N), S. typhimurium-infected mice (S), S. typhimurium-infected mice treated with F6 formula (F6) and F7 formula (F7) for 7 days. After 7 days of treatment, lymphocytes were isolated to determine the relative number of TGF-beta, interleukin (IL)-10, and TNF-alpha using flow cytometry analysis. The results showed that formulas 6 and 7 of CaCO3-reformulated i-bricks exhibited optimal physical properties, including density, compression, and water absorption. These formulas also inhibited the growth of S. typhimurium. Furthermore, formulas 6 and 7 possessed anti-inflammatory effects in S. typhimurium-infected mice indicated by the high increase in IL-10 and TGF-beta production and low levels of TNF-alpha. In conclusion, CaCO3 brick formulation can inhibit the growth of S. typhimurium and exert an anti-inflammatory effect. Further investigation is needed to reveal the effect of CaCO3-reformulated i-bricks on another inflammatory marker to further elucidate its anti-inflammatory mechanism.